2019
DOI: 10.1038/s41588-019-0493-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin activity at GWAS loci identifies T cell states driving complex immune diseases

Abstract: Immune disease variants are enriched in active chromatin regions of T cells and macrophages. However, whether these variants function in specific cell states is unknown. We stimulated T cells and macrophages in the presence of thirteen cytokines and profiled active and open chromatin regions. T cell activation induced major chromatin remodeling, while cytokines fine-tuned the Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 59 publications
9
81
0
Order By: Relevance
“…It entailed extensive changes in chromosome accessibility in regions enriched for regulatory elements and eRNAs, immune system-associated SNPs and TFBSs recognized by TFs involved in T cell development, activation or proliferation. What we demonstrate in human T cells parallels what has been described in other systems [1214,35,36] , namely that changes in chromatin accessibility in response to external cues identify active regulatory regions likely to be critical for transcriptional responses. Furthermore, we show that a T cell activation uncovers many additional regulatory regions likely to be associated with the immune response.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It entailed extensive changes in chromosome accessibility in regions enriched for regulatory elements and eRNAs, immune system-associated SNPs and TFBSs recognized by TFs involved in T cell development, activation or proliferation. What we demonstrate in human T cells parallels what has been described in other systems [1214,35,36] , namely that changes in chromatin accessibility in response to external cues identify active regulatory regions likely to be critical for transcriptional responses. Furthermore, we show that a T cell activation uncovers many additional regulatory regions likely to be associated with the immune response.…”
Section: Discussionsupporting
confidence: 86%
“…T cell activation is likely to be instructive of how coordinate changes in chromatin structure orchestrate gene expression programs that underlie rapid and often lifesaving responses. It was recently shown that T cell activation is associated with marked reorganization of chromatin structure at the level of accessibility (measured by ATAC-seq) [1214] and, separately, conformation (measured by promoter capture-Hi-C) [15] . The present study is the first to analyse genome-wide chromosome conformation in conjunction with chromatin accessibility and whole transcriptome expression, to understand how coordinated changes in higher- and lower-order chromatin structures are linked to gene expression in response to T cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…First, the species of T cells are different. Second, different methods, for example, blockade of costimulatory signals in mice by others (Liu et al, 2019) and treatment of healthy donors with G-CSF in our study (Jun et al, 2004), for tolerance induction via different signaling pathways might lead to differences in gene and TF expression (Liu et al, 2019; Soskic et al, 2019; Zhu and Paul, 2010). Overall, our study not only confirmed tolerance-inducing genes and TFs in human tolerant T cells, which were first observed in a mouse model, but also provided a platform to find novel genes, such as KLF-9.…”
Section: Discussionmentioning
confidence: 83%
“…Several of these loci cannot be resolved by fine-mapping 24 . Gene deserts were selected because: (1) less is known about how these predispose to disease compared to regions containing candidate genes, (2) other non-coding mechanisms (such as splicing effects 28 ) are unlikely to account for these associations, and (3) many of these contain epigenetic marks consistent with enhancer activity 9, 18, 29 . To maximise the genomic context tested around each SNP, we designed 3 overlapping constructs for every SNP allele 12 , and synthesised additional oligonucleotides to test combinations of risk alleles if more than one SNP could be assayed within the same construct.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we adapt an MPRA for use in resting and stimulated primary CD4 T cells – the cell-type whose regulatory DNA is most highly enriched for immune-mediated disease SNPs 2, 1618 . We use this method to simultaneously test individual candidate SNPs from 14 immune disease-associated gene deserts for expression-modulating activity.…”
Section: Introductionmentioning
confidence: 99%